Influence of surface pre-treatment on the deposition and corrosion properties of hydrophobic coatings on a magnesium alloy. (November 2016) - Zhang, Yufen; Blawert, Carsten; Tang, Shawei; Hu, Jin; Mohedano, Marta; Zheludkevich, Mikhail L.; Kainer, Karl Ulrich
Highlights: Pre-treatment prior to hydrophobic coating affects on the formation and growth of coating. Pre-treatments affect the thickness and morphology of coating rather than composition. Pre-treatment layer plays an important role in corrosion resistance of coated specimens. Abstract: Calcium stearate based hydrophobic coatings were deposited on pre-treated Mg alloy substrates. The influence of four different pre-treatments including plasma electrolytic oxidation (as prepared and etched), anodizing and hydrothermal treatment was studied. The results indicate that the pre-treatments have strong influences on the morphology, thickness, and wettability of the coatings, without affecting their phase composition. The coating system based on the etched plasma electrolytic oxidation pre-treatment shows the best corrosion resistance in a simulated body fluid. The superior protection effect is mainly related to the differences in the morphologies and thickness of the pre-treatment layers.